Extending social protection to informal economy workers Lessons from the Key Indicators of Informality based on Individuals and their Household (KIIbIH) - Kolev, Alexandre (OECD Publishing, 2023)
This paper exploits the information available in the OECD Key Indicators of Informality based on Individuals and their Household (KIIBIH) to shed light on several elements that could help inform national strategies for the extension of social protection to workers in the informal economy. It provides an assessment of current social protection coverage of informal workers throughout a large sample of developing and emerging economies and proposes a statistical framework to examine country-specific data, upon which a strategy for extending social protection to informal workers could be articulated. While the paper does not intend to provide detailed country-level recommendations, it highlights a number of important findings and policy directions as regards the way to extend non-contributory and contributory schemes to informal workers
Keywords: Employment; Social Issues/Migration/Health; Development